EFFECTIVENESS OF ANTI-DISCRIMINATION IMPLEMENTATION FOR LABOR IN MULTICULTURAL SOCIETY IN BATAM CITY FROM INTERNATIONAL AND NATIONAL LAW PERSPECTIVE - Azlyn, Nurul; Shahriyani Syahrullah, Rina; Syarief, Elza (Awang Long Law Review, 2025)
This study aims to evaluate the effectiveness of anti-discrimination policies in the workforce in Batam City, a center of industry with a high diversity of backgrounds. Although international and national regulations have been implemented to reduce discrimination, the practice of discrimination in the workplace is still a significant issue, as evidenced by the high rate of discrimination that occurs, including in Batam City. This study aims to analyze the application of international and national laws in Batam City because the industries in Batam City are comprised of local/national and foreign industries. This research uses a statutory approach and an empirical approach. The research was conducted through in-depth interviews with companies and agencies related to labor policies. The findings show that most companies in Batam City have adopted anti-discrimination policies to realize the international and national legal approaches. However, implementing these policies is often hampered by a lack of understanding and awareness of workers' rights, as well as weak monitoring mechanisms and sanctions for violations. This study recommends increased training on diversity and equality in the workplace, strengthened reporting mechanisms, and stricter law enforcement against perpetrators of discrimination. Thus, it is expected that a more inclusive and fair work environment can be created in Batam City.